Harmonisasi Hukum Islam dan Undang-Undang Perkawinan di Indonesia: Kajian Terhadap Usia Minimal Perkawinan - Nur, Syamsiah; Mudar, Andi Nadir; Hamdiyah, Hamdiyah; Munawar, Sofyan; Priyanto, Priyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam (IAI) Al-Aziziyah Samalanga, 2025)
This study discusses the harmonization between Islamic law and the Marriage Law in Indonesia, focusing on the minimum age of marriage. In Islamic law, the age limit for marriage is related to the concepts of baligh and rusyd, which, in classical fiqh, do not specify an exact number but depend on biological signs and intellectual maturity. Contemporary scholars, through the maqashid syariah approach, emphasize the protection of life, intellect, and lineage as fundamental principles in determining the appropriate age for marriage. In line with this, the amendment of the Marriage Law from Law No. 1 of 1974 to Law No. 16 of 2019 raised the minimum marriage age to 19 years for both men and women, considering health factors, children's rights, and the prevention of early marriage. This study analyzes the compatibility of this regulation with maqashid syariah and the challenges in harmonizing Islamic law with state law, including the marriage dispensation mechanism, which still allows room for underage marriages. Through an interdisciplinary approach, this study asserts that legal harmonization can be achieved through policies based on public welfare and child protection principles, ensuring that Islamic law remains relevant within the modern national legal framework.